EUROPA SPORTدور التجارة الإلكترونية في تعزيز مبيعات المؤسسة في ظل جائحة الكوفيد- 19 - دراسة حالة شركة - حنان نزار; شهرة زاد صمايدية (My University, 2022)
Many business organizations are moving into the world of e-commerce, where they are actively seeking to create their own websites with the aim of promoting and distributing their products and services through the Internet, but many of these organizations still suffer from certain obstacles that affect their sales volume. This study aims to clarify the relationship between the independent variable represented in e-commerce and the dependent variable represented in the sales of the organization in the light of the Covid-19 pandemic, where the descriptive analytical approach has been used in the theoretical and applied parts of the study, respectively, and to respond to the hypotheses of the study, a field study was carried out on a Europa sport company for the sale of sportswear, where the questionnaire tool was used to to know the opinions of the study sample composed of 30 individuals, and the results of this questionnaire were presented and analyzed using the SPSS program to test the validity of the hypotheses. By testing the hypotheses, the study concluded that there is a positive direct relationship between e-commerce and business sales in light of the Covid-19 pandemic. The study also recommended working on e-literacy and seeking to expand and develop e-marketplaces to facilitate transactions and open new e-markets. ............................................................. تتجو العديد من منظمات الأعمال نحو عالم التجارة الإلكترونية، حيث تسعى و بشكل فعلي لإنشاء مواقع إلكترونية خاصة بها بغرض ترويج وتوزيع منتجاتها وخدماتها عبر الانترنيت، إلا أن العديد من ىذه المنظمات لا زالت تعاني من بعض المعوقات التي تؤثر على حجم مبيعاتها. تهدف ىذه الدراسة إلى توضيح العلاقة بين المتغير المستقل المتمثل في التجارة الإلكترونية والمتغير التابع المتمثل في مبيعات المؤسسة في ظل جائحة كوفيد- 19 ، حيث تم استخدام المنهج الوصفي التحليلي في جانبي الدراسة النظري والتطبيقي على التوالي، وللإجابة على فرضيات الدراسة تم القيام بدراسة ميدانية على شركة Europa sport لبيع الألبسة الرياضية حيث تم استعمال أداة الاستبيان لمعرفة آراء عينة الدراسة المكونة من 30 فرد ، و تم عرض وتحليل نتائج ىذا الاستبيان باستخدام برنامج SPSS لاختبار صحة الفرضيات. من خلال اختبار الفرضيات توصلت الدراسة إلى وجود علاقة طردية موجبة بين التجارة الإلكترونية و مبيعات المؤسسة في ظل جائحة الكوفيد- 19 . كما أوصت الدراسة بالعمل على محو الأمية الإلكترونية، والسعي لتوسيع و تطوير الأسواق الإلكترونية لتسهيل المعاملات، و فتح أسواق إلكترونية جديدة.